Naturally Fermented Milk From Northern Senegal: Bacterial Community Composition and Probiotic Enrichment With Lactobacillus rhamnosus - Parker, Megan; Zobrist, Stephanie; Donahue, Chantal; Edick, Connor; Mansen, Kimberly; Hassan Zade Nadjari, Mehdi; Heerikhuisen, Margreet; Sybesma, Wilbert; Molenaar, Douwe; Diallo, Abdoulaye Moussa; Milani, Peiman; Kort, Remco (Frontiers in Microbiology, 2018)
A variety of foods fermented with lactic acid bacteria serve as dietary staples in many African communities, yet their bacterial profiles are poorly characterized. The integration of health-promoting probiotics into naturally fermented milk products could make a profound impact on human health. Here, we characterize the bacterial community composition of a naturally fermented milk product (lait caillé), prepared in wooden bowls (lahals) in northern Senegal, which is produced with a bacterial biofilm to steer the fermentation process. We incorporated a probiotic starter culture containing the most documented probiotic strain Lactobacillus rhamnosus GG (generic strain name yoba 2012) into the local fermentation process. Bar-coded 16S rRNA amplicon sequencing of lait caillé samples indicated that the bacterial community of lait caillé has a high species richness with over one hundred bacterial genera, however, few have high abundance. In contrast to the diverse bacterial compositions of other characterized naturally fermented milk products, the composition of lait caillé predominantly consists of the lactic acid bacteria Streptococcus and Lactobacillus, resembling the bacterial composition in regular yoghurt. The bacterial community composition of lait caillé varies geographically based on the presence of some genera, including Lactoccoccus, Enterococcus, Bifidobacterium and Bacillus, but this trend is not consistent within production communities. The diversity of bacterial communities is much higher in the lahal biofilm than in the naturally fermented milk products, which is in turn greater than commercial yoghurts. Addition of a starter culture with Lactobacillus rhamnosus yoba 2012 to lahals led to substantial growth of this probiotic bacterium in naturally fermented milk. Two independent quantitative PCR-analyses specific for Lactobacillus rhamnosus yoba 2012 indicated a 20 to 60-fold increase in the total number of probiotic bacteria in the first batch after inoculation. A similar increase of the probiotic was observed in a variation of lait caillé was prepared with carbohydrate-rich millet granules (thiakry) added prior to fermentation. This study shows the feasibility of integrating health-promoting probiotic strains into naturally fermented foods produced in regions with a high prevalence of malnutrition.